COVID-19 serological testing for Healthcare Workers in Lombardy, Italy. (30th September 2020) - Del Castillo, G; Castrofino, A; Grosso, F; Barone, A; Crottogini, L; Toso, C; Pellegrinelli, L; Pariani, E; Castaldi, S; Cereda, D
Abstract: Issue: COVID-19 pandemic began in Italy on February 20th, 2020. Since the beginning of the emergency Healthcare Workers' (HCWs) involvement was prominent, mainly due to direct assistance to COVID-19 patients. Therefore, we implemented a prevention policy for HCW screening through serological and RT-PCR testing. Description of the problem: HCW screening for SARS-CoV-2 infection is essential for prevention and control of the pandemic. Lombardy's Healthcare authorities settled a screening process for HCWs divided into three steps: 1) body temperature assessment at the beginning and the end of work shift, if fever > 37.5 °C was present the HCW was sent back home and a nasopharyngeal swab was performed; 2) progressive recruitment for serological testing; 3) on those positive to IgG a nasopharyngeal swab was performed and tested for viral RNA by RT-PCR. Results: Among 79185 HCW tested, 9589 (12%) were positive on serological IgG testing. Of the 9589 positive a nasopharyngeal swab was performed on 6884. Of these 358 (5%) tested positive and the remaining 6526 (95%) negative to RT-PCR. We calculated a Positive Predictive Value of 5.2%. The rate of positive serological tests for each Healthcare facility varied between 0% and 78%. Five percent of all facilities, belonging to Brescia, Bergamo and Cremona area, reported a positivity rate higher than 40% in HCWs. A second cluster (18% of all facilities), involving the same geographical area, reported a rate between 20% and 40%, whereas the remaining facilities (76%) of the region a rate <20%. Lessons: Serological IgG testing can be, if followed by immediate nasopharyngeal swab testing, a valid screening intervention on asymptomatic HCWs especially in a high infection prevalence setting. Key messages: Serological IgG testing can be, if followed by immediate nasopharyngeal swab testing, a valid screening intervention on asymptomatic HCWs. Infection prevention in HCW may benefit from a screening campaign especially in high prevalence settings.